1999
DOI: 10.4049/jimmunol.163.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Polyriboinosinic Polyribocytidylic Acid (Poly(I:C)) Induces Stable Maturation of Functionally Active Human Dendritic Cells

Abstract: For vaccination strategies and adoptive immunotherapy purposes, immature dendritic cells (DC) can be generated from adherent monocytes using GM-CSF and IL-4. Presently, the only clinically applicable method to induce stable maturation of DC is the use of supernatants of activated monocytes (monocyte-conditioned medium (MCM)). MCM contains an undefined mixture of cytokines and is difficult to standardize. Here we report that stable maturation of DC can be simply induced by the addition of polyriboinosinic polyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Unfortunately, no gold standard for effective DC maturation exists. Therefore, we used LPS gram-negative bacterial endotoxins (potent inflammatory mediators) [ 25 ], polyinosinic-polycytidylic acid (a synthetic double-stranded RNA analog that induces stable maturation of functionally active DCs) [ 26 ], and a cocktail maneuver including various cytokines [ 27 ]. Ultimately, we confirmed that the maturated DCs effectively activated T cells specific to certain antigens through IFN-γ secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, no gold standard for effective DC maturation exists. Therefore, we used LPS gram-negative bacterial endotoxins (potent inflammatory mediators) [ 25 ], polyinosinic-polycytidylic acid (a synthetic double-stranded RNA analog that induces stable maturation of functionally active DCs) [ 26 ], and a cocktail maneuver including various cytokines [ 27 ]. Ultimately, we confirmed that the maturated DCs effectively activated T cells specific to certain antigens through IFN-γ secretion.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that cDC2s upregulated RUNX3 along with CD207 and interferon response genes ISG15 , IFI30 , and IFITM3 in TC. We hypothesize that, in the TME, cDC2s are subjected to IFN-I dependent maturation, potentially via TLR stimulation as it occurs upon viral or poly I:C stimulation ( 71 , 72 ). Consistent with our observation at RNA level, CD207 + CD1a - cDC2s featured a more mature profile at protein level as compared to their CD207 - counterparts.…”
Section: Discussionmentioning
confidence: 99%
“… 187 189 In vitro, poly-I:C and poly-ICLC induce maturation of human peripheral blood monocyte-derived DCs, leading to secretion of IFN-β and the pro-inflammatory cytokines IL-6 and IL-12, resulting in cross-presentation of exogenous antigens with CD8 + T cells and triggering a Th1-polarized immune response. 190 , 191 Both preclinical and clinical studies have shown that poly-I:C and poly-ICLC are promising adjuvants that enhance antibody production and CD8 + T cell immune responses. 192 , 193 A test in humans showed that combining poly-ICLC with a DC-targeted vaccine induced an innate immune response similar to that of a live virus vaccine, further emphasizing the effectiveness of poly-I:C/poly-ICLC as vaccine adjuvants.…”
Section: Adjuvant Platforms Under Investigationmentioning
confidence: 99%